Rapamycin reverses hypertrophic cardiomyopathy in a mouse model of LEOPARD syndrome–associated PTPN11 mutation - Marin, Talita M.; Keith, Kimberly; Davies, Benjamin; Conner, David A.; Guha, Prajna; Kalaitzidis, Demetrios; Wu, Xue; Lauriol, Jessica; Wang, Bo; Bauer, Michael; Bronson, Roderick; Franchini, Kleber G.; et al. (The Journal of clinical investigation, 2011)
LEOPARD syndrome (LS) is an autosomal dominant "RASopathy" that manifests with congenital heart disease. Nearly all cases of LS are caused by catalytically inactivating mutations in the protein tyrosine phosphatase (PTP), non-receptor type 11 (PTPN11) gene that encodes the SH2 domain-containing PTP-2 (SHP2). RASopathies typically affect components of the RAS/MAPK pathway, yet it remains unclear how PTPN11 mutations alter cellular signaling to produce LS phenotypes. We therefore generated knockin mice harboring the Ptpn11 mutation Y279C, one of the most common LS alleles. Ptpn11(Y279C/+) (LS/+) mice recapitulated the human disorder, with short stature, craniofacial dysmorphia, and morphologic, histologic, echocardiographic, and molecular evidence of hypertrophic cardiomyopathy (HCM). Heart and/or cardiomyocyte lysates from LS/+ mice showed enhanced binding of Shp2 to Irs1, decreased Shp2 catalytic activity, and abrogated agonist-evoked Erk/Mapk signaling. LS/+ mice also exhibited increased basal and agonist-induced Akt and mTor activity. The cardiac defects in LS/+ mice were completely reversed by treatment with rapamycin, an inhibitor of mTOR. Our results demonstrate that LS mutations have dominant-negative effects in vivo, identify enhanced mTOR activity as critical for causing LS-associated HCM, and suggest that TOR inhibitors be considered for treatment of HCM in LS patients.